Evidence – Based Medicine (Practice/Care) - abubakr, muzdalifa; Basama, Basama (Gezira Journal of Health Sciences, 2007)
The medical decision–making process has, traditionally, been viewed as impressions of individual physicians, which is based on unsystematic observations and has been criticized as being inconsistent, leading to large variations in practice and inequality in services’ provision (Lockett, 1997). This has led to an increased demand for an effective, efficient, and accountable National Health Services (NHS) and healthcare that based on evidence. The concept of Evidence-Based Medicine (EBM) is old and relates to clinical trials (Lockett, 1997). The objectives of EBM are to; eliminate inconsistent, ineffective, unsafe, and expensive decision–making practices (Rosenberg and Donald, 1995). It aims at systematically locates, appraises, and uses the research findings to make informed clinical decisions (Roberts, 1999). The phrase EBM has originated from McMaster University in Canada. However, Evidence-Based Care (EBC) or Evidence-Based Practice (EBP) are preferable alternatives than EBM, as they encompass medical, nursing, and other aspects of health care. Cost Effective Medicine (CEM), which links cost to efficiency and effectiveness, has also been proposed as a synonymous to EBM (Lockett, 1997). The current evidence has shown that effective quality care raises the costs, but paradoxically the development of guidelines have been perceived as a drive to reduce costs (Newton et al, 1996).